Impact of Immunotherapies on SARS-CoV-2-Infections and Other Respiratory Tract Infections during the COVID-19 Winter Season in IBD Patients - Constanze Heike Waggershauser; Cornelia Tillack-Schreiber; Paul Weyh; Eckard Alt; Thorsten Siegmund; Christine Berchthold-Benchieb; Daniel Szokodi; Fabian Schnitzler; Thomas Ochsenkühn (Canadian Journal of Gastroenterology and Hepatology)
Background. COVID-19 represents one of the most significant medical problems of our time. Aims. This study is focused on the question whether patients with inflammatory bowel disease (IBD) who receive immunotherapies are more vulnerable to respiratory tract infections and SARS-CoV-2 infections in comparison to medical staff, as a cohort with an increased infection risk, and to the general population in a COVID-19 hotspot. Methods. We analysed data regarding respiratory tract infections that were collected in our IBD registry and compared them with corresponding data from medical employees in our associated Isarklinikum hospital and from the healthy general population in Munich, Germany, over the same time frame in April and June 2020. Patients were tested for SARS-CoV-2 immunoglobulins (Ig). Results. Symptoms of respiratory tract infections occurred equally frequent in IBD patients with immunotherapies as compared to those without. Older age (>49 years), TNF-inhibitor, and ustekinumab treatment showed a significantly protective role in preventing respiratory tract symptomatic COVID-19 infections that occurred in 0.45% of all our 1.091 IBD patients. Of those, 1.8% were positive for SARS-CoV-2 Ig, identically to the general population of Munich with also 1.8% positivity. Whilst more than 3% of all COVID-19 subjects of the general population died during the first wave, none of our IBD patients died or needed referral to the ICU or oxygen treatment. Conclusions. In our study, IBD patients are as susceptible to respiratory tract infections or SARS-CoV-2 as the normal population. There is no evidence of an association between IBD therapies and increased risk of COVID-19. Interestingly, a reduced rate of COVID-19 deaths in IBD patients, the majority on immunomodulator therapy, was observed, compared to the general population. Therefore, no evidence was found to suggest that IBD medication should be withheld, and adherence should be encouraged to prevent flares. In addition to older age (>49 years), TNF inhibitors and ustekinumab show a protective role in preventing respiratory tract infections. In addition, these results add to the growing evidence that supports further investigation of TNF inhibitors as a possible treatment in the early course of severe COVID-19.